Polskie e-ziny i sieciowe czasopisma fantastyczne (rekonesans) - Olkusz, Ksenia (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The article focuses on Internet magazines which specialise in fantasy. Nowadays many writers make their debut via Internet periodicals, although writers who are already well known to the public also publish there. It should be noted that online magazines are often regarded as a valuable form of artistic, journalistic and critical activity. Internet periodicals are often ephemeral creations whose existence can be put to an end thanks to many factors: when the formula runs out; when the editors no longer take interest in their work; when it is impossible to continue the enterprise because of various reasons which have nothing to do with publishing problems. Internet magazines can exist in both traditional and electronic form. Their role, i.a., is to provide information on literary and publishing activities related to the subject matter of the periodical. Online magazines can hold patronage over cultural events; promote writings of particular authors; engage in critical, literary and at times even publishing activities.